Penyuluhan Prinsip 3 J Diabetes Mellitus Pada Masyarakat RT 25 Kelurahan Sawah Lebar Kecamatan Ratu Agung Kota Bengkulu Provinsi Bengkulu - Yourenqe, Meta Melendia; Anggraini, Gita Santi; Pembayun, Fajar Resti; Efendi, Heru; Sudiyanto, Sudiyanto (Utami Publisher, 2024)
The dedication of this community was carried out in RT 25, Kelurahan Sawah Lebar, Queen's High Precinct, Bengkulu City, selected because of the presence of diabetes mellitus data among the elderly that was obtained from the data of the Puskesmas Sawah Working Area of Queen the Great Precincts, Bengulu City. After conducting public interviews, the problem of diabetes mellitus in RT 25 is largely due to age factors, lack of care for blood pressure checking on a routine basis because of busy work and limited public knowledge of the principle of 3J. Students discussed with the team of field tutors, the puskesmas, the head of RT, to determine the program to be implemented. The stage of implementation of dedication to this community was conducted with interviews to the head of RT 25 and the puskesmass (CI) parties related to the problems in RT 25 Kelurahan Sawah Bharat. He then made the determination of the program of activities through FGD (Focus Group Discussion) which will be carried out to deal with the problems that exist in RT 25 Sawah Bharar. Student approval will provide a pre-test questionnaire related to principle 3J. Then the questioning session is answered to the educated community. The final stage of this activity participants were given a post-test questionnaire. The rise in public knowledge of hypertension from 47.5% to 81.6% was seen from the average pre- and post-test questionnaire scores. The result is that the adoption of the 3J principle can increase the average knowledge of the public by 81.6%. Post-decade evaluations show that people are able to understand about the adoption of the 3J principle of determining the amount of daily calorie intake, choosing the type of low-sugar food and setting a meal schedule on a regular basis. Overall, this community service program has succeeded in achieving the main goal of raising public awareness in regulating dietary patterns according to the 3J principle. With significant indicators of success in increasing knowledge in the community, as well as knowledge of how to regulate a diet with the principle of 3J in diabetes mellitus.